P12.07 Delivering increased service provision: ippf experience of providing targeted technical support within existing srh service delivery points for strengthened sti-specific service provision. (13th September 2015) - McCartney, D; Andjelic, D; Singh, A
Abstract : Introduction: In 2013, the International Planned Parenthood Federation (IPPF) set out a strategy for increasing service provision across the IPPF Member Associations (MAs). A key service area identified for rapid scale-up was sexually transmitted infections (STIs). As a global service provider of sexual and reproductive health (SRH), the prevention and management of STIs has long been an integral part of IPPF's mission. However, the provision of services for STIs, other than HIV, has been a lower priority among many IPPF MAs in recent years. Methods: To support the strengthening of STI-specific services, small seed grants were provided to eight MAs covering all six of IPPF's geographical regions to conduct a rapid assessment of existing service delivery points. This action-oriented process enabled MAs to set their own goals and directions, and to prioritise interventions to address STIs through existing service delivery points. Specific assessments determined the current service capacity and identified technical assistance needs for increasing STI-specific service delivery. Results: The assessments of existing service delivery points gathered information on key issues affecting access, utilisation, and quality of care services for STIs, and identified staff training needs. Overall analysis led to the identification of specific deficiencies affecting service delivery and need for improving programme-level interventions including training and updating guidelines for STIs. Some key opportunities included the scaling-up of both syndromic management and etiological diagnosis in all service delivery points, strengthened integration with other SRH-related services, rollout of rapid diagnostic syphilis testing, and prioritising interventions for young people including vaccination, prevention and screening. Conclusion: With commitment and support, targeted technical assistance with limited resources enabled the development of strategic recommendations for scaling-up effective STI-specific services. A number of existing simple, effective, and cost-effective services were identified for implementation towards increasing quality STI services at existing service delivery points providing SRH services. Disclosure of interest statement: Nothing to declare.